Financial inclusion indicators affect profitability of Jordanian commercial banks: Panel data analysis - Ghaith N. Al-Eitan; Bassam Al-Own; Tareq Bani-Khalid (Economies, 2022)
Previous literature supports the view that the financial inclusion leads to economic growth and helps alleviate poverty; however, it is still unclear whether financial inclusion increases bank profitability. The study assumes that financial inclusion is significant in enhancing the economy and minimizing loan accounts, and along with this assumption, the deposit size decreases the Jordanian banks' profitability despite the fact that the financial services and access to them have no significant influence upon such profitability. The major profitability drivers examined in this study comprised financial inclusion and financial leverage. In this study, 13 Jordanian banks' data from 2009 to 2019 were examined to determine the above issue. The study applied fixed effects on a panel data regression model. The findings indicated that the number of loan accounts and size of deposits negatively and significantly impacted the profitability of the commercial banks in Jordan. However, the number of branches and ATMs had no significant effect on the bank's profitability. In sum, both leverage and bank size were the top two determinants of commercial banks' profitability in Jordan. Based on the findings, Jordanian policymakers can shift their focus to offering affordable financial services that support SMEs' loans and start-ups.
Keywords: 330; commercial banks; financial inclusion; financial leverage; financial services; Jordan; profitability